Ya veras! - Gutierrez, John R .; Rosser, Harry L. (Boston, MA, U.S.A. Heinle & Heinle Publishers, 1995)
Continues study of the Spanish language by utilizing everyday situations.
Includes index.
Keywords: Spanish language -- Textbooks for foreign speakers -- English